2018
DOI: 10.36076/ppj.2018.5.e573
|View full text |Cite
|
Sign up to set email alerts
|

Mexiletine Usage in a Chronic Pain Clinic: Indications, Tolerability, and Side Effects

Abstract: Background: Background: Intravenous lidocaine has multiple applications in the management of acute and chronic pain. Mexiletine, an oral lidocaine analogue, has been used in a number of chronic pain conditions although its use is not well characterized. Objectives: To report our experience using mexiletine in a chronic pain population, specifically looking at tolerability, side effects, and EKG changes. Study Design: Retrospective, cohort study. Setting: Multiple pain clinic locations in an integrated multispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…All these side effects were mild and resolved with stoppage of mexiletine. 12 A phase II trial conducted to evaluate the safety and tolerability of mexiletine with doses of 300mg per day and 900mg per day showed that mexiletine was safe at both the doses but was well tolerated only at 300mg per day dose. Adverse effects noted at doses of 900mg per day led to a higher rate of discontinuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these side effects were mild and resolved with stoppage of mexiletine. 12 A phase II trial conducted to evaluate the safety and tolerability of mexiletine with doses of 300mg per day and 900mg per day showed that mexiletine was safe at both the doses but was well tolerated only at 300mg per day dose. Adverse effects noted at doses of 900mg per day led to a higher rate of discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…Mexiletine also has a role in peripheral neuropathy and chronic pain. [11][12][13] Recently, it has been used in the treatment of sporadic amyotrophic lateral sclerosis. 14 Mexiletine has been used off-label for various painful conditions of chronic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Dyspepsia was the most common symptom but adjunctive treatment with proton pump inhibitors ameliorated this in most. Other adverse events were headache, palpitations, nausea and syncope but there were no serious adverse events and all side effects resolved when medication was discontinued [34,35]. ECG parameters between baseline and highest mexiletine dose levels did not change significantly and overall frequent ECG monitoring when on a stable dose of mexiletine was not deemed necessary.…”
Section: Mexiletinementioning
confidence: 95%